Moving to primary care at scale: Dianne Taylor. (2nd July 2019) - Hancock, Dave
Abstract : After 23 years as a practice manager Dianne Taylor completed a diploma course and became project manager for a 17-practice federation. She talked to Dave Hancock about the journey